A process evaluation of a "physical activity pathway" in the primary care setting - Bull Fiona C; Milton Karen E (BMC, 2010)
Abstract Background Let's Get Moving (LGM) is a systematic approach to integrating physical activity promotion into the primary care setting. LGM combines a number of recommended strategies to support behavior change including brief interventions, goal-setting, written resources, and follow-up support. This study involved a process evaluation of implementing LGM in UK general practice. Methods The LGM intervention was implemented in six general practices in London. Practices recruited patients either 'opportunistically' in routine consultations or by letter of invitation sent to patients on the hypertension disease register. A key component of the intervention was the delivery of a brief counselling session aimed at facilitating physical activity behaviour change. Data collection methods included electronic patient records, a practice survey and focus groups and interviews with practitioners. Results A total of 526 patients were considered for LGM, 378 via the 'opportunistic' recruitment method and 148 using the disease register approach. Patient interest in the brief counselling session was high although the actual delivery style and content varied between practitioners. Patients were directed towards a variety of physical activity opportunities including local leisure services and walking schemes. Conclusion The learning from this pilot should inform a revised update of the LGM protocols before the planned dissemination of the intervention which is outlined in the Governments 'Be Active, Be Healthy' physical activity strategy. A robust assessment of effectiveness involving an experimental design and behaviour change measures is also warranted prior to wider dissemination.